A new species of the palaemonid shrimp genus Palaemonella Dana, 1852 (Crustacea: Decapoda: Caridea) from Okinawa Island, Ryukyu Islands, Japan - Komai, Tomoyuki; Yamada, Yusuke (Zootaxa, 2015)
The palaemonid shrimp genus Palaemonella Dana, 1852 is currently represented by 21 formally described species worldwide, of which 17 species are known from the Indo-West Pacific. In this study, a new species, P. okunoi, is described and illustrated on the basis of two ovigerous female specimens collected from coastal waters in Okinawa Island, Ryukyu Islands, Japan, at depths of 5–30 m. The new species closely resembles P. hachijo Okuno, 1999, but the shorter rostrum, more anteriorly located postrostral teeth on the carapace, the presence of a pair of submedian teeth on the fourth thoracic sternite and the less slender pereopods distinguish P. okunoi n. sp. from P. hachijo. The discovery of the present new species raises the number of Japanese species of Palaemonella to eight. An updated key to the Indo-West Pacific species of the genus is presented.